The Impact of Work From Home on Employee Performance and Job Satisfaction - Wijaya, Wijaya; Lamsir, Seno; Miftah, Miftah; Setiawati, Liana; Mulyaraharjani, RA Shanti Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Changes in global work patterns that have occurred since the COVID-19 pandemic have brought about major transformations in the world of work, one of which is the implementation of Work From Home (WFH). WFH is a work system that allows employees to carry out their duties and responsibilities from home by utilizing communication and information technology. This phenomenon is not only a temporary solution to maintain the continuity of company operations, but also creates a new paradigm in human resource management. This study uses a quantitative method with an explanatory research approach. The population in this study were all employees who implement the Work From Home work system in companies/agencies in Indonesia. Data analysis was conducted using statistical software (SPSS). Based on the research results, it can be concluded that the implementation of Work From Home (WFH) has a positive and significant impact on employee performance and job satisfaction. WFH can improve employee performance, especially in terms of time flexibility, effective use of technology, and accuracy of task completion. WFH also increases employee job satisfaction, especially related to work-life balance, time efficiency, and transportation cost saving.